A moving algorithm for non-uniform deployment in mobile sensor networks. (29th June 2011) - Liu, Cheng-Hung; Ssu, Kuo-Feng; Wang, Wei-Tong
Previous research indicated that uniform deployment was not the most efficient way for saving energy in wireless sensor networks (WSNs). The location nearer a sink should have more sensors deployed. This paper describes a moving algorithm for achieving the non-uniform deployment (MAND). With MAND, mobile sensors can move to appropriate locations to prolong the system lifetime. With two refinements on MAND (called EMAND), not only the coverage of the network is maintained, but the lifetime can be improved enormously. Simulation results show that EMAND performs well in the environment with more sensing events.